Optimizing the Eradication of Human Trafficking in Batam City: A Comparison of Indonesian and Singaporean Laws - Neha Aswin Maysura; Yudhi Priyo Amboro; Nurlaily Nurlaily (Kosmik Hukum, 2025)
Human Trafficking is a global issue that continues to escalate, including in Batam City, one of Indonesia's Human Trafficking hotspots. This study aims to analyze the effectiveness of combating Human Trafficking Crimes (Human Trafficking) in Batam City by comparing Indonesian and Singaporean laws. The research addresses the implementation of Indonesian laws, regulatory comparisons between the two countries, and recommendations for ideal solutions.The study employs normative and empirical legal methods with legislative, conceptual, and sociological approaches. Data were collected through literature reviews and interviews with relevant institutions in Batam. The findings reveal that although Indonesia’s Law No. 21 of 2007 provides a comprehensive legal framework, its implementation faces challenges such as weak inter-agency coordination, limited support facilities, and low public legal awareness. In comparison, Singapore has more effective regulations with severe sanctions and advanced technology. Recommendations include revising specific articles in Law No. 21 of 2007, strengthening cross-sectoral coordination, enhancing victim protection facilities, providing intensive training for law enforcement officers, and applying technological support. These measures are expected to optimize the fight against Human Trafficking in Batam City.